Understanding the Union - McLean, I (Oxford University Press, 2020)
Varieties of unionism in Scotland may be found in the debates in the last Scottish Parliament in 1705–1707 and persisted for three centuries. In modern politics, they may be roughly mapped to social unionism, trade and security unionism, and nationalist unionism. The three strands map poorly on to contemporary party labels but are conceptually coherent. A social union entails uniform welfare standards and a uniform safety net throughout the UK. The trade and security union is about the economies of scale generated by free trade within the UK. It used also to be about the military and the British Empire, to which Scots contributed massively, but has been reborn as a primordial concern for the Union in and of itself, but with added Faslane. Nationalist unionism insists on the integrity of Scots constitutional law and on the sovereignty of the Scottish people. It remains a live strand of unionism, although the least-understood one.